The human rights based approach to climate change mitigation: legal framework for addressing human rights questions in mitigation projects - Olawuyi, D (2013)
Over the last decade, the effects of an unprecedented rise in global temperature due to climate change, on the enjoyment of human rights, especially the right to life, have been subjects of intensive scholarly attention. Gallons of juristic ink have been spilled on the need for States to adopt policy measures aimed at combating climate change. However, recent findings show that policy measures and projects aimed at mitigating climate change are in turn producing even more serious human rights concerns, especially in developing countries. These human rights issues include: mass displacement of citizens from their homes to allow for climate change mitigation projects; lack of participation by citizens in project planning and implementation; citing and concentration of projects in poor and vulnerable communities; lack of governmental accountability on projects and the absence of review and complaint mechanisms for victims to obtain redress for these problems. These secondary human rights impacts of policy measures and projects aimed at mitigating climate change have not received sufficient attention in existing literature. The aim of this research is to examine and analyse the effects of climate change mitigation projects, specifically Clean Development Mechanism (CDM) projects, on the enjoyment of fundamental human rights. It considers how lessons from the approval and execution of CDM projects could inform thoughts on the value and requirements for mainstreaming human rights safeguards into international climate change regimes in general. It analyses the legal and theoretical prospects and paradoxes of adopting the United Nations Human Rights Based Approach (HRBA) as a framework through which human rights standards may be systemically integrated and mainstreamed into extant and emerging international legal regimes on climate change.